Study on the postoperative visual function recovery of children with concomitant exotropia based on an augmented reality plasticity model - Lv, Xiu-Fang; Zhong, Hui; Yang, Hao-Jiang; He, Li; Xiong, Mei; Zhang, Xiao-Ling; Wang, Li; Fang, Wang; Wu, Jin (Frontiers in Psychology, 2023)
Objective: This study aimed to investigate the clinical application effect of an augmented reality (AR) plasticity model on the postoperative visual function recovery of children with concomitant exotropia. Methods: Between September 2019 and October 2021, 28 patients with concomitant exotropia who visited Shenzhen Children's Hospital (9 male and 19 female) were enrolled in this study. The average age of the patients was 6.4 ± 1.8 years. Postoperative rehabilitation training was conducted using a personalized AR binocular visual perception plasticity model developed based on the patient's examination results. After 1 month, 3 months, and 6 months of training, the patients returned to the hospital for examinations of perceptual eye position, static zero-order stereopsis, dynamic first-order fine stereopsis, and dynamic second-order coarse stereopsis to compare the changes in eye position control and stereovision function. Results: After 6 months of eye position training, the horizontal perception eye position of the 28 patients was significantly lower than that before training. The difference in eye position at the first and third months compared with that before training was not statistically significant (1st month: z = −2.255, P = 0.024 > 0.017; 3rd month: z = −2.277, P = 0.023 > 0.017; 6th month: z = −3.051, P = 0.002 < 0.017). The difference in vertical perceptual eye position after training compared with that before training was not statistically significant (1st month: z = −0.252, P = 0.801 > 0.017; 3rd month: z = −1.189, P = 0.234 > 0.017; 6th month: z = −2.225, P = 0.026 > 0.017). The difference in 0.8-m static zero-order stereopsis before and after training was not statistically significant (1st month: z = −2.111, P = 0.035 > 0.017; 3rd month: z = −1.097, P = 0.273 > 0.017; 6th month: z = −1.653, P = 0.098 > 0.017). The 1.5-m static zero-order stereopsis was improved after 1 month, 3 months, and 6 months of training compared with that before training (1st month: z = −3.134, P = 0.002 < 0.017; 3rd month: z = −2.835,P = 0.005 < 0.017; 6th month: z = −3.096, P = 0.002 < 0.017).